2000
DOI: 10.1136/ewjm.172.5.301
|View full text |Cite
|
Sign up to set email alerts
|

Survivors of torture in a general medical setting: how often havepatients been tortured, and how often is it missed?

Abstract: Survivors of torture in a general medical setting: how often have patients been tortured, and how often is it missed?ABSTRACT ⅷ Objectives To measure the frequency of people reporting torture among patients in a medical outpatient clinic and to determine primary care physicians' awareness of their patients' exposure to torture. ⅷ Design Cross-sectional survey followed by selected in-depth interviews of participants reporting a history of torture. Medical record review and interview of torture survivors' primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 9 publications
1
43
1
1
Order By: Relevance
“…However, it has previously been found that general practitioners are unaware of the implications of patients having a refugee background and that they often refrain from enquiring further about the refugee situation [24]. In addition, there is also evidence that indicates that torture and other traumatic incidents experienced by the patients may be missed by the general practitioners [22,23]. Contrary to these findings, some of the health professionals in our study expressed that they are aware of the importance of considering a traumatic background in regards to their refugee patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has previously been found that general practitioners are unaware of the implications of patients having a refugee background and that they often refrain from enquiring further about the refugee situation [24]. In addition, there is also evidence that indicates that torture and other traumatic incidents experienced by the patients may be missed by the general practitioners [22,23]. Contrary to these findings, some of the health professionals in our study expressed that they are aware of the importance of considering a traumatic background in regards to their refugee patients.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors of torture may not easily share their stories on their own initiative [21]. Furthermore, several studies show that general practitioners are uncertain whether a refugee background is of importance in relation to the health of their patients [22-24] and that they are reluctant to initiate conversations about traumatic experiences in relation to the situation in their home countries, their escape and their life in exile [24]. …”
Section: Introductionmentioning
confidence: 99%
“…The first task is to recognize the torture survivor: we know that most go unrecognized [4, 5]. It is often estimated that at least 30 % of refugees have been subject to torture or organized violence, yet refugees are rarely asked about experiencing violence.…”
Section: Pain From Torturementioning
confidence: 99%
“…[3][4][5] In the United States, there are over 500,000 foreign-born torture survivors, and about 20 percent of these live in New York City's metropolitan area. 3 Torture, in the human right context, is defined as acts that cause intense physical or psychological pain, are volitional, are done to punish or coerce, and are sanctioned actively or passively by governments or their agents. Although 5-11% of foreign-born patients at US urban medical centers are torture survivors, doctors often are unaware of this medically relevant information.…”
Section: Introductionmentioning
confidence: 99%